Determination of computed tomography number of high-density materials in 12-bit, 12-bit extended and 16-bit depth for dosimetric calculation in treatment planning system. Issue 3 (19th February 2019) - Jayamani, Jayapramila; Osman, Noor Diyana; Tajuddin, Abdul Aziz; Salehi, Zaker; Ali, Mohd Hanafi; Abdul Aziz, Mohd Zahri
Abstract: Aim: The main aim was to examine the effect of bit depth on computed tomography (CT) number for high-density materials. Analysis of the CT number for high-density materials using 16-bit scanners will extend the CT scale that currently exists for 12-bit scanners and thus will be beneficial for use in CT–electron density (ED) curve in radiotherapy treatment planning system (TPS). Implementation of this extended CT scale will compensate for tissue heterogeneity during CT–ED conversion in treatment planning. Materials and methods: An in-house built phantom with 10 different metal samples was scanned using 80, 100 and 120 kVp in two different CT scanners. A region of interest was set at the centre of the material and the mean CT numbers together with data deviation were determined. Dosimetry calculation was performed by applying a direct anterior beam on 12-bit, 12-bit extended and 16-bit. Results: High-density materials (>4·34 g cm −3 ) in 16-bit depth provide disparities up to 44% compared to Siemens' 12-bit extended. Influence of tube voltage showed a significant difference ( p <0·05) in both bit depth and CT number of the gold and amalgam saturated in 16-bit depth. A 120 kVp energy illustrated a low variation on CT number for different scanners, but dosimetry calculation showed significant disparities at the metal interface in 12-bit, 12-bit extended and 16-bit. Findings: High-density materials require 16-bit scanners to obtain CT number to be implemented in treatment planning in radiotherapy. This also suggests that proper tube voltage together with correct CT–ED resulted in accurate TPS algorithm calculation.